2007
DOI: 10.1136/thx.2007.079608
|View full text |Cite
|
Sign up to set email alerts
|

Protection from experimental ventilator-induced acute lung injury by IL-1 receptor blockade

Abstract: Background: Clinical studies have shown that injurious mechanical ventilation is associated with increased airspace and plasma levels of interleukin-1b (IL-1b); however, the potential therapeutic value of IL-1 inhibition in acute lung injury has not been thoroughly investigated. A study was undertaken to determine if IL-1 signalling is a necessary early event in the pathogenesis of experimental ventilator-induced lung injury. Methods: Mice deficient in IL-1 receptor type 1 (IL1R1) and rats treated with IL-1 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
100
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 46 publications
7
100
2
Order By: Relevance
“…Many studies have shown that severe lung injury is provoked by ventilation with high tidal volumes. [15][16][17] Although the exact underlying mechanisms of VILI remain undefined, several potential pathways have been proposed, with barotrauma appearing to be the generally accepted one. In our study, significant infiltration of neutrophils was observed on pathological examination of the lung tissue exposed to high tidal volume ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that severe lung injury is provoked by ventilation with high tidal volumes. [15][16][17] Although the exact underlying mechanisms of VILI remain undefined, several potential pathways have been proposed, with barotrauma appearing to be the generally accepted one. In our study, significant infiltration of neutrophils was observed on pathological examination of the lung tissue exposed to high tidal volume ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β expression augments neutrophil recruitment and also impairs fluid clearance via down-regulation of the epithelial sodium channel (ENaC) [94]. Early blockage of IL-1β is protective in a murine model of VILI, suggesting that IL-1β may be a potential target in ALI [92]. However, IL-1β has some roles in epithelial wound repair [95,96], and further evaluation of its role in both the pathogenesis and resolution of ALI is needed.…”
Section: Release Of Other Proinflammatory Mediatorsmentioning
confidence: 99%
“…Other inflammatory mediators, such as IL-1β, have been found to be upregulated in animal models of ALI as well as in BAL fluid from patients with ARDS [92,93]. IL-1β expression augments neutrophil recruitment and also impairs fluid clearance via down-regulation of the epithelial sodium channel (ENaC) [94].…”
Section: Release Of Other Proinflammatory Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…KC and MCP-1 are chemotactic signals for neutrophils, which contribute to the development of VILI [17,18]. IL-1β was shown to induce endothelial permeability and aggravate VILI [19]. IL-6 is upregulated under mechanical ventilation and, although its exact role in VILI remains controversial, IL-6 levels are correlated with organ failure and outcome in ARDS [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%